Antenatal risk factors, cytokines and the development of atopic disease in early childhood. Issue 1 (21st December 2006) - Chung, E K; Miller, R L; Wilson, M T; McGeady, S J; Culhane, J F
Abstract : Atopic diseases are complex entities influenced by an array of risk factors, including genetic predisposition, environmental allergens, antenatal exposures, infections and psychosocial factors. One proposed mechanism by which these risk factors contribute to the development of atopic disease is through changes in the production of T helper cell type 1 (Th1) and T helper cell type 2 (Th2) cytokines. The objectives of this review are to discuss antenatal exposures that are associated with paediatric atopic diseases, to discuss the influence of the intrauterine environment on neonatal immune responses, to provide an overview of the Th1 and Th2 pathways and how they relate to atopic disease, and to summarise our current understanding of the association between cytokine responses in cord blood and the development of atopic disease in early childhood.